ADULT LEARNERS’ MOTIVATION TO LEARN A FOREIGN LANGUAGE - Naumčiuk, Toma (PROFESSIONAL STUDIES: Theory And Practice, 2023)
Research on peculiarities how adults learn foreign languages in formal, non-formal and informal ways is comparatively not extensive, especially in Lithuania. Therefore, it was important to investigate the effects which motivate adults to learn foreign languages and how age makes a difference in learning. A research survey was designed on the basis of theoretical analysis and the study was conducted in Kaunas and Panevezys cities in order to find out the reasons why participants learn foreign languages (i.e. their extrinsic or intrinsic, integrative or instrumental motivation). The results of the empirical study revealed that adult foreign language learners in Lithuania mostly learn the English language and they know Russian and German; the current language they are learning in many cases is their second or third one. The participants revealed that adult learners are mostly motivated intrinsically (because of their wish to improve, learn, travel and etc.), less adults were motivated extrinsically (because of the work purposes – instrumental motivation) and because of communication reason (integrative motivation). The survey showed that participants believe that to learn a foreign language it is important to be motivated, want to improve in their life and, of course, to have a purpose.